Sepsis in Obstetrics: Treatment, Prognosis, and Prevention. Issue 4 (July 2017) - Parfitt, Sheryl E.; Bogat, Mary L.; Roth, Cheryl
Abstract : Abstract: Sepsis during pregnancy is one of the five leading causes of maternal mortality worldwide. Early recognition and prompt treatment of maternal sepsis is necessary to improve patient outcomes. Patient education on practices that reduce infections may be helpful in decreasing rates of sepsis. Education of nurses about early signs and symptoms of sepsis in pregnancy and use of obstetric-specific tools can assist in timely identification and better outcomes. Although the Surviving Sepsis Campaign (SSC) criteria for diagnosis of sepsis in the general population are not pertinent for obstetric patients, their treatment bundles (guidelines) are applicable and can be used to guide care of obstetric patients who develop sepsis. This article is the third in a series of three that discuss the importance of sepsis and septic shock in pregnancy. This article includes case studies, treatment, prognosis, education, and prevention of maternal sepsis. Abstract : Sepsis during pregnancy is one of the five leading causes of maternal mortality world-wide. Early recognition and prompt treatment are necessary to improve patient outcomes. Case studies, treatment strategies, prognosis, suggestions for education for clinicians and patients, and recommendations to prevent maternal sepsis are included.